Conditioned secure access control model based on multi-weighted roles and rules in workflow system (Tongxin xuebao)
The traditional RBAC model cannot express complicated workflow secure access control constraint, so a new conditioned RBAC model suit for WfMS （workflow management system）—CMWRRBSAC （conditioned multi-weighted role and rule based secure access control model） was proposed on the basis of multi-weighted roles and rules. Based on the traditional RBAC model, a conditioned RBAC method was discussed on the basis of dynamic role assignment and a new concept of workflow access authorization was defined on the basis of multi-weighted roles. A sort algorithm based on token and a sort algorithm based on weighted roles synthesis were presented in allusion to the problem of multi-roles and multi-users sequence constraint in the process of executing tasks. A rule-based modeling method of separation of du- ties was discussed and its improved rule consistency check arithmetic was given.